A Study Of TQM On Tourism Websites - Mirhossein, Elham (2010)
The main focus of this study is on the quality aspects in tourism electronic market places. Furthermore, this exploratory survey employs quantitative research to discover the relevant issue in tourism Websites challenges. It also seeks to identify the quality concerns related to the services, content and design of the tourism Websites. This study depicts a broad picture of significant issues and challenges of quality management in Tourism Website